2012
DOI: 10.1507/endocrj.ej12-0030
|View full text |Cite
|
Sign up to set email alerts
|

Role of orexin in the central regulation of glucose and energy homeostasis [Review]

Abstract: Abstract. Hypothalamic orexin neurons are known to regulate sleep/wake stability, feeding behavior, emotions, autonomic nerve activity, and whole-body energy metabolism. In addition, emerging evidence indicates that orexin contributes to central regulation of glucose homeostasis. Intriguingly, central administration of orexin is reported to cause blood glucoseelevating effect or blood glucose-lowering effect in rodents, depending on the experimental conditions. Here we reviewed the recent reports regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…Tsuneki et al suggested that orexin-expressing neurons effectively response to nutritional conditions and increase the expression of orexin mRNA precursors in the condition of hunger and low blood sugar caused by insulin in lateral hypothalamus of mice (10). In agreement with this study, our findings showed coordinated changes in OXA and plasma levels of glucose, so that increase in OXA was associated with reduction in blood glucose.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tsuneki et al suggested that orexin-expressing neurons effectively response to nutritional conditions and increase the expression of orexin mRNA precursors in the condition of hunger and low blood sugar caused by insulin in lateral hypothalamus of mice (10). In agreement with this study, our findings showed coordinated changes in OXA and plasma levels of glucose, so that increase in OXA was associated with reduction in blood glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have shown that physical activity can play an important role in the regulation of glucose homeostasis by affecting the adipoinsular axis and effective peptides on this axis such as OXA (9). A recent evidence indicated that the disruption of OXA production is an effective factor in glucose homeostasis and diabetes induced by ageing (10). Since OXA is a factor in integrating peripheral metabolism, central regulation of behaviors, and maintenance of energy homeostasis (11).…”
Section: Introductionmentioning
confidence: 99%
“…52 Orexins/hypocretins bind to two G-protein-coupled receptors 53 named orexin receptor 1/2 (ORXR1/2) or hypocretin receptor 1/2 54 (HcrtR1/2) which are ubiquitously expressed (pituitary gland, kidney, 55 adrenal, thyroid, testis, ovary, jejunum, and lung) (Johren et al, 2001) 56 indicating that orexins/hypocretins may regulate several physiological 57 processes (Johren et al, 2001). Indeed, mammalian orexins/hypocretins 58 have been shown to regulate energy homeostasis (energy intake and 59 expenditure) (Sakurai et al, 1998;Dube et al, 1999;Haynes et al, 60 2000;Rodgers et al, 2002;Thorpe et al, 2003), arousal and wakefulness 61 (Chemelli et al, 1999;Lin et al, 1999), glucose and lipid metabolism 62 (Tsuneki et al, 2008;Tsuneki et al, 2010Tsuneki et al, , 2012, circadian clock (Belle (ACTH) and corticosterone in rat (Kuru et al, 2000;Bonnavion et al, 73 2015). However, regulation of the orexin system by stress itself remains 74 largely unexplored in most species.…”
mentioning
confidence: 99%
“…Moreover, orexin appears to be involved in the maintenance of insulin sensitivity, because orexindeficient male mice fed normal chow diet exhibited agerelated development of systemic insulin resistance despite normal body weight (17,18), and because orexin-deficient narcoleptic patients with cataplexy showed BMI-independent metabolic alterations, including insulin resistance (19). However, the role of orexin in glucose homeostasis remains elusive, since orexin A is reported to cause the blood glucose-elevating and -lowering effects in rodents depending on the experimental conditions (20)(21)(22). We hypothesized that orexin has the ability to promote generation of the glucose rhythm via bidirectional regulation of HGP.…”
mentioning
confidence: 99%